Coastline Change in the Banyuasin Estuary Over the Last Three Decades - Heron Surbakti; I Wayan Nurjaya; Detriech G Bengen; Tri Prartono; Andi Agussalim; Riris Aryawati; Robinson Sitepu; Raisyah Salsabilah (Jurnal Ilmu Lingkungan, 2025)
Coasts or shorelines are sites of dynamic activity, and phenomena such as wave and tidal action, sediment supply rate, sea level changes, and the morphological characteristics of the area play a critical role in shaping coastal ecosystems. This study examines coastal changes along the Banyuasin Estuary in South Sumatra, Indonesia, over 30 years (1989–2019). We use remote sensing data, machine learning, and the DSAS tool to analyze historical changes (1989-2019). Landsat images obtained from the United States Geological Survey (USGS) via the Google Earth Engine API are analysed using ArcGIS and DSAS 6.0 software. The largest rate of change occurred at Anakan Island, with the most significant accretion rate being 118.98 m/year, causing a shoreline change of 2012.33 m over 30 years. The smallest shoreline changes were in the Telang and Payung Island areas, which are located in the Musi River Estuary. The magnitude of maximum shoreline change in both locations was 62.72 m and 92.34 m, respectively, with maximum rates of change ranging from 2.09 - 3.08 m/year. The results show that the general pattern of accretion-abrasion in the Banyuasin Estuary is divided into three stages: rapid accretion stage (1989-1994), accretion-erosion adjustment stage (1994-2009), and slow erosion stage (2009-2019).